Blended learning strategies in teaching general pathology at a medical course - Juliana A. Fermozelli; Mario Luis R. Cesaretti; Maria Lourdes P. Barbo (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introdution: In many medical schools, it is evident that learning of general pathology is deficient, mainly due to the disinterest in knowledge not directly related to professional practice and the lack of pedagogical resources that motivate learning. Blended learning (BL) is an active method of hybrid teaching that uses different technological resources, promoting greater dynamism and integration of students. Objective: The objective of this research was to evaluate, from the perspective of the students of the medical course of Pontifícia Universidade Católica de São Paulo (PUC-SP), the motivation and the capacity to contextualize provided by the employment of BL to the teaching of general pathology. Material and method: The BL sessions were performed during the applied in-class activities of pathology in the period from October 6 to 31, 2014, in the Neoplasms Module, with the second-year students of the medicine course at PUC-SP. Results: Most of the students showed acceptance of the method, greater motivation and ability to contextualize the pathological processes. Conclusion: The use of BL can provide students with greater contextualization of pathology in medical practice, contributing to a more meaningful learning.